Compilation of Sarawak Tua Pek Kong Temples Layouts. 砂拉越大伯公廟平面圖匯集 - Chai, Elena Gregoria Chin Fern (Sibu En An Teng Association, 2014)
Temple is a material product of culture. This material product is subjective to changes by people. Each Chinese community in Sarawak adopts their own sense of livelihood, thus creating their very own local culture. All this coud be exemplified through the temple culture. However, due to social change temple culture is going through an ongoing process of change. The changes could be seen firsthand through the physical structure of the temple. This book serves as a baseline data for my future research. The compilation of layouts for all 76 Tua Pek Kong temples reveal the structure of the main hall of each temple. The setting of the main altar, side altars, worship tables, and others all differ vastly. The positions and names of deities in each temple are shown beneath the layouts. In 5 years time, the layouts of the temples will be remeasured, and analysed to review the changes that has taken place in the temple, and its community.